Analysis of Factors Affecting the Work Performance of Bangkalan Pratama KPP Employees (Work Performance Factors: Job Design, Compensation System, and Work Motivation) - Nawang Furyshade; Kuswandi; Sri Rahayu; Rifda Fitrianty (International Publisher, 2025)
This study examines the influence between job design, compensation system, and work motivation on employee performance at work. The sample in this study were 77 employees at the Bangkalan Primary Tax Service Office. In writing this thesis, the author uses primary data collection techniques, which are obtained by distributing Likert scale questionnaires. This study uses multiple linear regression analysis using the statistical application SPSS (Statistical Package for the Social Sciences) version 22. The results showed that partially the job design variables, the compensation system, and work motivation had a significant effect on employee performance, at the Bangkalan Primary Tax Service Office simultaneously the job design variables, the compensation system, and work motivation. Simultaneously, job design variables, compensation system, and work motivation affect employee work performance, at the Bangkalan Primary Tax Service Office.